Evaluation of accurate indoor localization systems in industrial environments - Karaagac, Abdulkadir; Haxhibeqiri, Jetmir; Ridolfi, Matteo; Joseph, Wout; Moerman, Ingrid; Hoebeke, Jeroen (2017 22nd IEEE International Conference on Emerging Technologies and Factory Automation (ETFA), 2017)
Due to the fast emergence of location-based services and the absence of a widely adopted localization technology for indoor environments, Indoor Localization Systems have become a central topic of research in the last decade. Although there is a significant amount of research targeting indoor localization technologies and their performance, most of these efforts only focus on theory, system design or evaluation in non-industrial environments, usually offices or healthcare spaces. In this work, a detailed performance evaluation of two commercially available accurate localization technologies, based on Bluetooth Low Energy (LE) and Ultra-wideband (UWB), in an industrial environment is presented to create an experimental understanding of their behaviour in similar conditions and to investigate their potential to be used in industrial applications with concrete localization requirements. For this purpose, these localization technologies are examined with respect to various performance criteria in several scenarios in a real industrial site.